Pembuatan Website Penyedia Layanan Bisnis Digital “Usaha Pelajar” Menggunakan Framework Codeigniter - Syamsi Ruhama; Faris Nurfadillah (Jurnal Indonesia Sosial Teknologi, 2022)
Student Business is a provider of digital product services such as credit, quotas, PLN tokens, and others. One of the efforts to improve service and member registration for student businesses is to create a website. On the website, users can register without having to wait for the manual verification process from the admin. Student business service users have difficulty in purchasing because they have to wait for verification from the admin first. The purpose of this research is to create a student business tool/website to make it easier for admins to manage sales directly and users become members without having to wait for the verification process. The website was created using the SDLC waterfall method with the stages of needs analysis, system design, implementation, program testing, operation and maintenance. Student business website consists of member and admin pages. Members can directly select and buy the desired product efficiently. This student business website can make it easier for members to register and make it easier for admins to sell via the internet.